IMPACT OF BODY MASS INDEX ON GLYCEMIC CONTROL AND THYROID FUNCTION - Ayesha Qaisar; Muhammad Asghar; Haseeb Ullah; Nazia Shahana; Henna Salman; Naila Hamid (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Diabetes mellitus and thyroid dysfunction are both endocrine dysfunction, both of the complementing each other in one way or another with increase in BMI affecting them both.1 Objective: To assess the effect of BMI on  glycemic control and thyroid function Materials And Methods: This cross sectional study was conducted at almost all the major tertiary care hospitals of Peshawar from January 2017 to April 2017. This was preceded by fulfilling the ethical dilemmas in the form of approval from ethical board of Khyber Medical University Peshawar and obtaining institutional consent. A total of 358 individualswere taken using non probability consecutive sampling. 179 of them were type 2 Diabetics and 179 were healthy non diabetic subjects and then comparison was made between two groups to see the correlation between them in terms of thyroid dysfunction and glycemic control. Mean and SD were applied for quantitative variables and frequency and percentages were applied for qualitative ones. Pearson correlation was used to see effect of BMI on glycaemic control and thyroid function and their mutual correlation with a p value of 0.05 or less as significant. Results: The mean age of cases and controls was 54.35 ± 9.38 years and 42.66 ± 9.20 years; on comparing their median (as data was not normal) we found higher median age of cases when cases and controls were compared, p-value < 0.0001.p-value = 0.002In cases there were 6(3.4%) underweight, 90(50.3%) had normal weight, 51(28.5%) were overweight and 32(17.9%) cases were obese. There was significant correlation BMI and TFTS and HBA1c as reflected by a p value of 0.02 . Conclusion: Increase in BMI had a significant impact on both HBA1C and thyroid function tests which emphasizes the need for screening such patients.